2004
DOI: 10.1542/peds.113.5.e435
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the Risk of Postneonatal Death in the United States

Abstract: ABSTRACT. Objective. Breastfed infants in the United States have lower rates of morbidity, especially from infectious disease, but there are few contemporary studies in the developed world of the effect of breastfeeding on postneonatal mortality. We evaluated the effect of breastfeeding on postneonatal mortality in United States using 1988 National Maternal and Infant Health Survey (NMIHS) data.Methods. Nationally representative samples of 1204 infants who died between 28 days and 1 year from causes other than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
165
1
12

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(180 citation statements)
references
References 22 publications
2
165
1
12
Order By: Relevance
“…20 A proportion (21%) of the US infant mortality has been attributed, in part, to the increased rate of SIDS in infants who were never breastfed. 21 That the positive effect of breastfeeding on SIDS rates is independent of sleep position was confirmed in a large case-control study of supine-sleeping infants. 22,23 It has been calculated that more than 900 infant lives per year may be saved in the United States if 90% of mothers exclusively breastfed for 6 months.…”
Section: Sudden Infant Death Syndrome and Infant Mortalitymentioning
confidence: 90%
“…20 A proportion (21%) of the US infant mortality has been attributed, in part, to the increased rate of SIDS in infants who were never breastfed. 21 That the positive effect of breastfeeding on SIDS rates is independent of sleep position was confirmed in a large case-control study of supine-sleeping infants. 22,23 It has been calculated that more than 900 infant lives per year may be saved in the United States if 90% of mothers exclusively breastfed for 6 months.…”
Section: Sudden Infant Death Syndrome and Infant Mortalitymentioning
confidence: 90%
“…In many instances there is no other choice for families and, still, even in industrialised western countries without the intense breast feeding and physical monitoring that accompanies co-sleeping, the survival of an infant is threatened. For example, Chen and Rogan 68 found that, even in the USA where infectious diseases do not seriously threaten the lives of infants, approximately 750 American infants die in the first year of life because they were not breast fed. Mothers and infants sleeping side-by-side, cosleeping, continues to be the universal (species-specific) evolved context that best provides maximum night-time breast feeding nutrition for the highly immature and slow developing human infant.…”
Section: Toward Clarifying Definitions and Discourse On Mother-infantmentioning
confidence: 99%
“…Breastfeeding decreases the risk of sudden infant death [8] , necrotizing enterocolitis, and other neonatal infections [14] , while protecting against cardiovascular disease [27] , atopic disease [33] , and obesity [10] . It may even improve cognitive development [3] .…”
Section: Introductionmentioning
confidence: 99%